KEDUDUKAN HUKUM PENGAMBILALIHAN TANAH WAKAF YANG BATAL DEMI HUKUM UNTUK DIBAGIKAN SEBAGAI HARTA WARISAN DALAM KAJIAN UNDANG-UNDANG NO. 41 TAHUN 2004 TENTANG WAKAF - Lambang Prasetyo (Universitas Semarang, 2017)
ABSTRACTWakaf is legal act of a person or legal entity that separates part of the property in the form of land property and institutionalize it forever for the sake of worship or other public purposes in accordance with the teachings of Islam. The purpose of this study is: To understand the process of the acquisition ofwakaf land which is canceled by law for being shared as heritage and the legalstatus of wakaf land acquisition which is canceled by law for being shared asheritage in accordance with Act No. 41 Year 2004 about wakaf. The research methodology used in this study is juridical normativeapproach, with specification of analytic descriptive. The sources of the researchare derived from the primary and secondary law materials with the technique ofcollection through the literature and library research. The method of datapresentation is descriptive, the method of analyzing the law materals is done byusing qualitative analysis. The results of the research show that: 1) The process of acquisition of wakafland that is canceled by law for being shared as inheritance is carried out bySemarang Religious Court by determining the joint property of wakif and thewakif‟s wife, then set half of the joint property is the wakif part which has notbeen shared and stated the heirs and their parts according to the provision ofIslamic inheritance. This is in accordance with Article 97 of the Compilation ofIslamic Law which states that the wakif (widower) should be given half of thecommon property as long as it is not specified otherwise in the marriageagreement. 2) Legal status of the acquisition of wakaf land which is canceled bylaw for being shared as inheritance based on Act No. 41 Year 2004 about wakaf,In principle, Act No.41 Year 2004 affirms that wakif‟s land that has been sharedcan not be canceled, but of course the principle of law certainty must synergizewith the value of fairness to the perpetrator or heirs. This is where the role of the judges are required to provide fair justice if found wakaf case.